The isolation and identification of the important pathogenic bacteria from fresh meat: Aseel M. Hamzah , Maysoon Sabah Abbas , Waffa A.Ahmed - Hamzah, Aseel M. (The Iraqi Journal of Veterinary Medicine, 2010)
This study was aimed to investigate the load of bacterial contaminant in fresh meat with different types of bacteria.One handered and seven samples were collected from different regions of Baghdad . These samples included 37 of fresh beef 70 of fresh sheep meat. All samples were cultured on different selective media to identitfy of contaminated bacteria .The result revealed that The percentage of bacterial isolate from raw sheep meat were,23.8 % of StreptococcusgroupD, 29.4 % of Staphylococcus aureus ,14.7 % of E.coli 4.9 , % of Salmonella spp, , 3.5 % of pseudomonas aeruginosa14.7 , % . 14.7 % of Proteus spp. 2.1 % of Listeria spp while the raw beef meat content 5.55 % of Staphylococcus aureus, 8.14 % of Streptococcus group D , 1.85 % 5.18 % of E.coli, 3.7 % of Proteus spp 1.85 ،% of Salmonella spp1.85% of pseudomonas aeruginosa، . 1.48 % of Bacillus cereus and.1.48 % of Klebsiella spp